Effective control of microstructure evolution in AZ91D magnesium alloy by SiC nanoparticles in laser powder-bed fusion. (August 2021) - Niu, Xiaomiao; Shen, Hongyao; Fu, Jianzhong; Feng, Jiawei
Graphical abstract: Highlights: SiCnp controlled the grains' growth mode in the laser melted AZ91D. SiCnp has dramatically refined the grain size of the additively manufactured AZ91D. Fully equiaxed growth of the grains has been achieved by adding SiCnp. The strength of the AZ91D-SiCnp materials was higher than the nanoparticle-free ones. Abstract: Laser Powder-Bed Fusion (LPBF) of Mg-Al alloys is a promising way to additively manufacture Mg-Al alloy components. However, the grains of the LPBF-processed AZ91D Mg-Al alloys could be coarse. The grains might undergo columnar growth, which is less resistant to hot tearing than equiaxed growth. Refining the microstructure by manipulating the processing parameters requires extensive experimental work. In this study, we used SiCnp-decorated AZ91D powder to additively manufacture AZ91D-SiCnp composites. The nanoparticles react with the melt, ensuring a high density of nucleation sites. The nanoparticles at the solid–liquid interface significantly blocked the diffusion of Al solute atoms, leading to solute enrichment at the interface. The remaining melt undercooled to a greater extent comparing with the nanoparticle-free melt, thus more potential nucleus were activated. As a result, columnar-to-equiaxed transition of the grains' growth has been achieved and the grains' size has reduced significantly by assembling SiCnp onto the feedstock AZ91D powder. In conclusion, AZ91D-SiCnp composites with desirable microstructure and mechanical properties have been successfully manufactured by LPBF.